Shattering man’s fundamental assumptions in Don DeLillo’s Falling Man - Hashim, Hazim Adnan; Talif, Rosli; Hameed Ali, Lina (Australian International Academic Centre, 2016)
The present study addresses effects of traumatic events such as the September 11 attacks on victims’ fundamental assumptions. These beliefs or assumptions provide individuals with expectations about the world and their sense of self-worth. Thus, they ground people’s sense of security, stability, and orientation. The September 11 terrorist attacks in the U.S.A. were very tragic for Americans because this fundamentally changed their understandings about many aspects in life. The attacks led many individuals to build new kind of beliefs and assumptions about themselves and the world. Many writers have written about the human ordeals that followed this incident. Don DeLillo’s Falling Man reflects the traumatic repercussions of this disaster on Americans’ fundamental assumptions. The objective of this study is to examine the novel from the traumatic perspective that has afflicted the victims’ fundamental understandings of the world and the self. Individuals’ fundamental understandings could be changed or modified due to exposure to certain types of events like war, terrorism, political violence or even the sense of alienation. The Assumptive World theory of Ronnie Janoff-Bulman will be used as a framework to study the traumatic experience of the characters in Falling Man. The significance of the study lies in providing a new perception to the field of trauma that can help trauma victims to adopt alternative assumptions or reshape their previous ones to heal from traumatic effects.